Three microporous metal–organic frameworks assembled from dodecanuclear NiII6LnIII6 subunits: synthesis, structure, gas adsorption and magnetism. Issue 43 (3rd October 2018) - Feng, Dan-Dan; Dong, Hui-Ming; Liu, Zheng-Yu; Zhao, Xiao-Jun; Yang, En-Cui
Abstract : Three microporous MOFs with two different orientated {Ni II Ln III }6 subunits exhibit high Ln III -independent gas uptake and absorption selectivity for CO2 as well as Ln III -dominated slow magnetic relaxation and a magnetic cryogenic magnetocaloric effect. Abstract : Three isostructural heterometallic metal–organic frameworks (MOFs) {[Ln2 Ni(OAc)5 (HL)(L)]·solvent molecules} n (H2 L = 2-hydroxyimino- N -[1-(2-pyrazinyl)ethylidene]-propanohydrazone, Ln = Dy for1, Tb for2 and Gd for3 ) were solvothermally synthesized by varying rare-earth metal ions with different electron configurations. Their crystal structures, gas adsorption and magnetic behaviors were fully investigated. The three isomorphous MOFs exhibit three-dimensional microporous frameworks with two different orientated dodecane metallic {Ni II Ln III (HL)}6 metallomacrocycles alternately connected by {Ln III (L)} connectors, in which an empty one-dimensional channel decorated by the basic hydrazone interior is generated. Due to their Ln III -independent microporous nature, the activated sample of1 as a representative example has a significant CO2 uptake up to 42.2 cm 3 g −1 and an unusually high CO2 /N2 and CO2 /CH4 adsorption selectivity of up to 98.8 and 16.8 at 298 K and 100 kPa. Magnetically, apparent antiferromagnetic interactions for both1 and2 as well as ferromagnetic coupling for3 are respectively observed at low temperature resulting from the competition of magnetic anisotropy and intermetallic ferromagnetic superexchange. Additionally, 1 with highly anisotropic Dy III spin shows slow magnetization relaxation under zero dc field, whereas3 possessing isotropic Gd III ions displays a significant cryogenic magnetocaloric effect with a maximum entropy change of 26.6 J kg −1 K −1 at 3.0 K and 70 kOe. These interesting results can provide valuable information on gas separation-based multifunctional 3d–4f MOF materials.